1. The problem statement, all variables and given/known data How to simplife it? I would like to see a process of simplification. Y = A'B'C'D + A'B'CD + A'BC'D + A'BCD' + A'BCD + AB'C'D + AB'CD + ABC'D' The ' denotes a bar over the previous letter. My second question is: Y = BC + AB'D = (uploaded picture) Y = A'D + B'D + A'BC + ABC'D' = ??????? 2. Relevant equations Simplification Rules 3. The attempt at a solution I tried it but can't get to the correct result. The correct result should be (made through Karnaugh map): Y = A'D + B'D + A'BC + ABC'D' Thank you for any advices and I'm sorry for my english.